The Effect Of Supervision And Standard Operational Procedures (SOP) On Employee Performance With Work Discipline As An Intervening Variable - Erika Widyastutie; Nurul Qomariah; Ni Nyoman Putu Martini (UNIVED Press, 2025)
The goals of the organization are not only dependent on technology, but more dependent on the human resources who carry out their work. The ability to provide optimal work results to meet the needs of the organization as a whole is a contribution to employee performance. Having employees who have good performance and quality is the hope of every leader in order to achieve the goals of the organization. This study aims to test and analyze the effect of supervision and Standard Operating Procedures (SOP) on employee performance with work discipline as an intervening variable in the Nursing section of the Kalisat Regional Hospital. The population used in this study were all employees in the Nursing section of the Kalisat Regional Hospital and the sample size was 130 respondents. The method of analysis and hypothesis testing uses variance-based SEM testing or Partial Least Square (SEM-PLS) with the WARP-PLS program. The results showed that supervision has a positive and significant effect on employee performance and work discipline. Standard Operating Procedures (SOPs) have a positive and significant effect on work discipline but are not significant to employee performance. Work discipline has a positive and significant effect on employee performance. Supervision and Standard Operating Procedures (SOP) have a positive and significant effect on employee performance with work discipline as an intervening variable.